Strategi Pemasaran Kawasan Pecinan Surya Kencana Bogor sebagai Destinasi Wisata Budaya - Siska Rosalisa; Made Adhi Gunadi; Meizar Rusli (Journal of Tourism Destination and Attraction, 2015)
historic buildings, Chinese festival, heritage cuisine and old town atmosphere that’s so unique you can not find in other places in Bogor City. Besides its potential cultural attraction and heritage cuisine, Suryakencana Bogor Chinatown Region has potential historic tourism that moulded Suryakencana Region until present time dan has so many Chinese and European-mixed architectured buildings. Until now, those potential are still present, but slowly forgotten because the region is not not well-ordered and well-managed yet. All of those cultural tourism potential will be more visible and prominent to tourists if the cultural tourism potentialsare marketed by the right marketing strategy costumized with the tourist interests whose visited to the region. The used research method is mixed method. The research shows that the right segment for marketing Suryakencana Bogor Chinatown Region is the family with children segment because they are the frequent tourists who visited Suryakencana Bogor Chinatown Region for tasting the culinary in Bogor, thus the potential marketing segment for Suryakencana Bogor Chinatown Region.